Making Crime a Sustainable Development Issue: From ‘Drugs and Thugs' to ‘Peaceful and Inclusive Societies' - Blaustein, Jarrett (The British journal of criminology, 2020)
Development has long featured on the United Nations (UN) crime policy agenda; however, crime was only officially recognized by the international community as a global development priority following the adoption of the Sustainable Development Goals in 2015. Adopting a sociological institutionalist perspective, this article sets out to account for how this recognition was achieved. We draw on interviews with senior UN crime policy insiders and documentary sources to analyse the efforts of the United Nations Office on Drugs and Crime (UNODC) to amplify awareness of the crime-development link following the omission of this issue from the Millenium Development Goals and amidst significant institutional and material pressures to strengthen its ties to the wider UN system. The article accounts for the political construction of the crime-development nexus and the important role that UNODC has historically played in facilitating global governance in this emergent and increasingly expansive sphere of policy and practice.